Posttraumatic Stress Disorder Is Highly Comorbid With Adult ADHD in Alcohol Use Disorder Inpatients. Issue 11 (September 2021) - El Ayoubi, Hussein; Brunault, Paul; Barrault, Servane; Maugé, Damien; Baudin, Grégoire; Ballon, Nicolas; El-Hage, Wissam
Objective: Increasing number of studies show an association between adult ADHD (a-ADHD) and posttraumatic stress disorder (PTSD). We explored this association in alcohol use disorder (AUD) inpatients.Method: In total, 551 inpatients cross-sectionally completed self-administered questionnaires regarding sociodemographics, lifetime trauma exposure, PTSD Checklist for DSM-5, Adult ADHD Self-Report Scale (ASRS), and Wender Utah Rating Scale (WURS). We considered self-reported a-ADHD when ASRS and WURS had significant scores.Results: Prevalence for a-ADHD was 20%. PTSD prevalence was higher in a-ADHD patients (84% vs. 40%; p < .001). They also were younger ( p < .001) and women ( p = .015). Adult ADHD was associated with more traumatic events, and symptoms were correlated with PTSD severity. After adjusting for age, gender and marital status, PTSD severity was associated with a-ADHD.Conclusion: Our study confirms that a-ADHD is associated with PTSD in AUD inpatients, and thus, may represent a specific subpopulation. Future studies should explore implication of this dual diagnosis on AUD and treatment outcome.